Effect of Bubble Contact Diameter on Bubble Departure Size in Flow Boiling. Issue 1 (2nd January 2016) - Guan, P.; Jia, L.; Yin, L.; Tan, Z.
Abstract : The growth and departure of bubbles on a vertical heated wall of an annular channel in flow boiling were observed by a high-speed camera, and the bubble contact diameter and bubble departure diameter were measured. It was found that bubble departure diameters were different among different nucleation sites in the same boiling area (same test condition, same surface roughness). Force balance on a single bubble attached to the heated surface was also analyzed to explain this phenomenon. The theoretical research results show that bubble contact diameter has a significant influence on bubble departure diameter, and the corresponding departure diameter is larger as the bubble contact diameter is larger. This agrees with the visual experimental results.